From childhood nature experiences to adult pro-environmental behaviors: An explanatory model of sustainable food consumption. Issue 8 (2nd August 2020) - Molinario, Erica; Lorenzi, Caterina; Bartoccioni, Flavia; Perucchini, Paola; Bobeth, Sebastian; Colléony, Agathe; Diniz, Raquel; Eklund, Ann; Jaeger, Christine; Kibbe, Alexandra; Richter, Isabel; Ruepert, Angela; et al.
Abstract: In two studies, the role of nature experiences and social norms during childhood is explored next to adulthood biospheric values, connectedness to nature, environmental identity, and objective knowledge in relation to pro-environmental behaviors. Study 1 ( N = 185) tested the hypothesized model in the realm of general pro-environmental behaviors and sustainable fruit consumption on a sample of students. Study 2 ( N = 155) tested the model in the realm of sustainable seafood consumer choice on a general population sample. Path analyses show consistent results across samples. Results show that childhood nature experiences and exposure to pro-environmental social norms during childhood are related to adulthood development of connectedness with nature and biospheric values; these, in turn, help in shaping adulthood environmental self-identity ultimately influencing the enactment of sustainable food choices during adulthood. These findings point toward the relevance of childhood experiences for pro-environmental behaviors as compared to the provision of information. The role of objective knowledge across samples is inconsistent, thus requiring future investigations.